Swedish and International Arbitration 1990 - Rudholm Sten (Arbitration Institute of Stockholm, 1990)
The Taba Tribunal, The Arbitration Institute of the Stockholm Chamber of Commerce, The Arbitral Tribunal, Salient Features of the Swedish Arbitral Procedure, Arbitration and the Swedish Courts.